Um estudo sobre os egressos do curso de Mestrado no Programa de Pós-Graduação em Educação: Currículo - 2013-2020 - Abi Rached, Maria Aparecida da Silva (2022)
The study of the relation between academic education and professional performance of graduates with the proposals of the Master’s stricto sensu courses represents, nowadays, increasingly pertinence and importance. This is so because the Graduate Programs, including the Master’s Program in Education: Curriculum of the Pontifícia Universidade Católica de São Paulo (PUC-SP), need, given current issues, to focus on this relational process in order to understand professional and social demands in greater depth. Thus, the objective of this study is to measure the possible impacts related to the training and performance of the Master of Education: Curriculum, from the profile of graduates from the period 2013-2020, in view of their academic and professional paths, as indicators to the incorporation of new demands and propositions to the Graduate Program in Education: Curriculum of PUC-SP. The theoretical foundation that supports the present investigation is based on the contributions of the following works: Apple (1999); Chizzotti (2013); Feldmann (2009, 2018); Feldmann, Masetto and Freitas (2016); Freire (2006); Lousada and Martins (2005), Martins and Noffs (2018); Pena (2000); Perrenoud (2013); Ribeiro (2005); Sacristán (2017); Tardif (2014), among others. From the methodological point of view, it is a qualitative investigation with a descriptive and interpretive nature, which involves bibliographic and documentary research and field study. Among the research findings, the importance of implementing a policy for monitoring graduates that addresses the dynamics of current professional and social demands as well as continuing education programs aimed at graduates of the Program stand out